GENDER SPECIFICITY OF COLORECTAL CANCER IN THE REPUBLIC OF TATARSTAN - B. I. Gataullin; R. Sh. Khasanov; A. A. Savelyev; I. G. Gataullin (Сибирский онкологический журнал, 2021)
The purpose of the study: to develop an expert system based on the construction of a «decision tree» for predicting the 5-year survival rate of patients with colorectal cancer.Material and Methods. T he study included 654 patients with colorectal cancer (CRC) who were treated from 2013 to 2015, including 434 men and 220 women. The average age of patients was 64,1 ± 10,2 years. All patients underwent genetic analysis for the presence of a mutation in the K-ras gene from the primary tumor.Results. For the Republic of Tatarstan, there are regional features of mutation of the K-ras gene: the frequency of mutations in tumors in men was less frequent (20.3 %) than in women (37.7 %), in patients of Slavic nationality, mutations were slightly more frequent – 39 % than in Tatars – 21 %. The gender approach to assessing long-term treatment results showed that in men with colorectal cancer, the most favorable treatment results were observed in patients with tumors in stage T1–2N0M0, regardless of the differentiation of the tumor and its mutational status. Low-grade tumors with any T should be considered prognostically unfavorable in men, with the presence of regional metastases and mutation of the K-ras gene, even in the absence of distant metastases: no patient lived 5 years. Based on the construction of a «decision tree», the most favorable treatment results were observed in female patients with tumors in stage T1–2–3N0M0 at the age of 70 years (5-year survival rate of 90 %), with tumors T1–2N0M0 at the age of 70 years (5-year survival rate of 81.8 %), regardless of the tumor differentiation and its mutational status. Tumors of any differentiation are prognostically unfavorable for women of the T3–4N0 stage with the presence of distant metastases (6 % of patients lived 5 years) and lowdifferentiated stage T4N0M0 tumors (5-year survival rate of 8 %).Conclusion. G ender- and age-associated features of the development and course of CRC are relevant for oncologists to choose effective diagnostic and therapeutic measures.